Evaluasi Penerapan Sistem Informasi Manajemen Rumah Sakit Pada Instalasi Farmasi Rsud Cilacap Dengan Metode End User Computing Satisfaction (Eucs) - Windi Antika; Jason Merari Peranginangin; Pudiastuti RSP (An-Najat, 2024)
SIMRS is used to process and integrate all hospital services using system networks, reporting, and management or administration flows to obtain accurate information. Evaluation of the information system at Cilacap Regional Hospital was carried out to see whether the information system had been implemented well or not. The End User Computing Satisfaction (EUCS) method is used to compare user expectations and realities regarding information systems in order to determine the level of satisfaction. This research uses a descriptive method with a quantitative approach. This research method uses cross sectional. The research instrument used was a questionnaire. The sample for this research consisted of 48 users. The independent variables consist of content, accuracy, format, ease of use, and timelines. The dependent variable is the level of user satisfaction. Data analysis was carried out using correlation tests and multiple linear regression tests. Based on the results of the correlation test, the variables content, accuracy, format, ease of use, and timelines have a significant relationship with the level of SIMRS user satisfaction. Based on the multiple linear regression test, the variables content, accuracy, format, ease of use, and timelines together have a significant relationship with the level of satisfaction. Multiple linear regression model Y=5.610 + 0.129X1 + 0.143X2 + 0.201X3 + 0.462X4 + 0.3479X5.